Masked face identification using face recognition - Hossen, Tareq; Uddin, Abbas; Barua, Niloy; Faik, Chowdhury Azmain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.